2022
DOI: 10.3390/ijerph19095687
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions Associated with Brain Imaging Markers in Patients with Psoriasis

Abstract: Psoriasis is a severe inflammatory disease associated with a higher comorbidity of depression, cognitive dysfunction and brain atrophy. The association between psoriasis, magnetic resonance imaging (MRI) markers and cognitive impairment has rarely been investigated, and the existing results are conflicting. Methods. This study included 89 subjects (53 patients with psoriasis and 36 healthy controls). The severity of psoriasis was evaluated using the Psoriasis Area and Severity Index (PASI) score; for depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Our results showed diminished cognitive functions in various domains for processing speed, attention, memory and executive function in patients with psoriasis, which is supported by prior studies. 7,9,10,12,[34][35][36] A prior study also identified an association between cognitive impairment and depression. 37 However, our study showed no association between cognitive decline and depression (GAD7), anxiety (PHQ9) or sleep quality (PSQI) scores.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results showed diminished cognitive functions in various domains for processing speed, attention, memory and executive function in patients with psoriasis, which is supported by prior studies. 7,9,10,12,[34][35][36] A prior study also identified an association between cognitive impairment and depression. 37 However, our study showed no association between cognitive decline and depression (GAD7), anxiety (PHQ9) or sleep quality (PSQI) scores.…”
Section: Discussionmentioning
confidence: 91%
“…We found the clinical severity indicators of psoriasis especially the PASI score being significantly correlated with cognitive testing scores, which was generally in line with a prior study. 34 Psoriasis and cognitive impairment have been linked through the chronic inflammation process 38,39 and aberrant immune response. 11 In addition, a more severe status of psoriasis may be associated with a greater risk of comorbidities such as cardiovascular disease, diabetes, obesity, etc., 40 which were high-risk factors for cognitive impairment.…”
Section: Characteristicsmentioning
confidence: 99%
“…A few studies have analyzed the psychological status of middle-aged and young patients with dermatosis; generally, young patients pay more attention to appearance, and their emotional state is more linked to changes in appearance ( 20 ). It was reported that old patients with skin pruritus mostly showed type A behavior, who were prone to being nervous and anxious, and were not able to cope with this situation ( 21 , 22 ). Pruritus is an unpleasant feeling of the skin or mucous membrane that causes a desire to scratch.…”
Section: Discussionmentioning
confidence: 99%
“…PsA is found in one out of every five psoriasis patients, and the joints such as elbows, knees, scalp, lumbosacral areas, intergluteal clefts and glans penis are affected in up to 30% of patients 6 . Psoriasis is also linked to an increased risk of depression, cognitive impairment and brain atrophy 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 Psoriasis is also linked to an increased risk of depression, cognitive impairment and brain atrophy. 7 Psoriatic arthritis (PsA) belongs to a group of rheumatological disorders characterised by a variety of clinical symptoms and pathologies that can impair a patient's quality of life. 8 This inflammatory arthritis is a heterogeneous, chronic, inflammatory musculoskeletal condition that destroys function towards the peripheral and axial joints, with no universally accepted classification or diagnostic criteria for axial involvement in PsA, and no agreement on treatment paradigms, increasing the difficulty of PsA management.…”
mentioning
confidence: 99%